Program Sedekah Jumat Untuk Menumbuhkan Empati Anak Usia Dini - Ikmila, Miladia Maulaya; Hidayatu Munawaroh; Siti Lailiyah (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
Education is a planned effort for self-development and prepares students to learn new and useful things for their respective lives. Education in schools through learning activities, training, guidance, practice and so on. While early childhood education is the provision of stimulation by educators to develop physical motor, religious and moral, cognitive, language and social emotional aspects. In the learning process with children, parents or teachers usually detect children who experience a problem that must be prevented from early childhood, one of which is the problem of the lack of development of early childhood empathy at Pertiwi I Kalibeber Kindergarten, Empathy is a person's sensitivity to feel something that other people feel too. Students who lack a sense of empathy tend not to want to help others, do not want to apologize when wrong, do not care if they harm others. The cultivation of empathy in early childhood is very important to prevent this, therefore the Friday alms program at school can slowly foster empathy in early childhood. The formulation of the problems in this study are 1) How is the application of Friday alms activities to foster empathy in early childhood at Pertiwi I Kalibeber Kindergarten 2) How is the impact of Friday alms to foster early childhood empathy at Pertiwi I Kalibeber Kindergarten 3) What are the supporting and inhibiting factors for Friday alms activities at Pertiwi I Kalibeber Kindergarten? The purpose of this study was to determine 1) the application of Friday alms to foster empathy for early childhood in Pertiwi I Kalibeber Kindergarten, 2) the impact of alms to foster empathy for early childhood in Pertiwi I Kalibeber Kindergarten, 3) and find out the supporting and inhibiting factors of Friday alms activities in Pertiwi I Kalibeber Kindergarten. In discussing this thesis using a qualitative field approach with data collection techniques carried out by observation, interview and documentation methods. The subjects in this study were class B students in the 20203/2024 school year at Pertiwi I Kalibeber Kindergarten. Data analysis in this study is to use the Data Triangulation Technique. The results of this study reveal three findings which include: 1) The application of Friday alms to foster early childhood empathy at Pertiwi I Kalibeber Kindergarten. 2) The impact of Friday alms to foster early childhood empathy at Pertiwi I Kalibeber Kindergarten. 3) Supporting and inhibiting factors for Friday almsgiving at Pertiwi I Kalibeber Kindergarten.